FACTORS ASSOCIATED WITH BODY MASS INDEX IN CHILDREN – A COMMUNITY-BASED STUDY - PALADUGU, NIKHILA; RAYITI, RAMAKRISHNA; NUTAKKI, SIDDHARTHA; GADDE, RAJASREE; K, SAILAJA; GHANTA, VIJAYA KUMAR; SRUJANI KANAGALA, VISWA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: The increasing prevalence of overweight, obesity, and underweight in children has implications for their future health and it is vital to understand the modifiable factors that contribute to it. The study’s main objective is to determine the factors associated with the body mass index in children. Methods: A cross-sectional study was conducted among 346 school children over a period of 6 months. Data were collected using self-administered questionnaire. Physical measurements such as height and weight were obtained from parents. Body mass index was calculated using kg/m2. Children were categorized as overweight, obese, normal, and underweight using their body mass index scores and the factors associated with BMI in children were estimated. Results: The prevalence of overweight, obesity, normal, and underweight among children was 10.40%, 17.92%, 24.28%, and 41.67%, respectively. Intake of fast food, sweetened beverages, junk food, and consumption of food while watching television, media time indicated a significant relationship with body mass index. Conclusion: Health care professionals should educate parents and children regarding healthy nutrition and regular physical activity. The implications of obesity, overweight, and underweight should be well explained to make desirable lifestyle modifications for a better future.